Correction: The preventive effect of linalool on acute and chronic UVB-mediated skin carcinogenesis in Swiss albino mice. Issue 11 (24th October 2019) - Gunaseelan, Srithar; Balupillai, Agilan; Govindasamy, Kanimozhi; Muthusamy, Ganesan; Ramasamy, Karthikeyan; Shanmugam, Mohana; Rajendra Prasad, N.
Abstract : Correction for 'The preventive effect of linalool on acute and chronic UVB-mediated skin carcinogenesis in Swiss albino mice' by Srithar Gunaseelan, et al., Photochem. Photobiol. Sci., 2016, 15, 851–860.